ELASTOGRAPHY IN TA TIGHTNESS TO EVALUATE MUSCLE PHYSIOLOGY – A DIAGNOSTIC APPROACH (Journal of Pharmaceutical Negative Results, 2022)
Shear wave elastography is useful for treating the musculoskeletal system. This drug is used to treat tendonitis, ligamentitis, and muscle pain. In the human body, the Achilles tendon is the strongest. The quantity and incidence of Achilles tendon overuse injuries and total ruptures in developed countries has increased in recent decades, owing to the fact that most Achilles tendon injuries occur in sports and there has been a general increase in sporting activity. Tendinopathy is the most common clinical diagnosis for Achilles tendon overuseinjuries, and it is marked by pain and swelling in the Achilles tendon, as well as an inability to engage in strenuous activities. Nonoperative treatment is helpful for the majority of people with Achilles tendon injuries, and those who do not respond to nonoperative treatment require surgery. In sports that demand jumping, running, and fast turns, a complete rupture of the Achilles tendon is common. Blue, green, and yellow/red are the color associated with rigid, intermediate, and soft tissue, respectively.Colour mapping will help us in rehabilitation .